2001
DOI: 10.1182/blood.v98.5.1489
|View full text |Cite
|
Sign up to set email alerts
|

Role for lipid rafts in regulating interleukin-2 receptor signaling

Abstract: IntroductionLipid rafts are plasma membrane microdomains postulated to function in signaling and membrane trafficking. [1][2][3] Lipid rafts are enriched in gangliosides (glycosphingolipids) and cholesterol, which form liquid-ordered domains of decreased membrane fluidity. The long, saturated acyl chains of gangliosides impart a high degree of order further stabilized by intercalating cholesterol molecules, leading to the insolubility of lipid rafts in nonionic detergents. Lipid rafts can be isolated based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 42 publications
2
95
1
Order By: Relevance
“…It has been reported that IL-2 pulls out the ␣ chain from rafts to bind the ␤ and ␥ chain of the IL-2 receptor complex in soluble fractions (50). Hence, interleukins are involved in the rules governing the inclusion and exclusion of proteins into rafts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-2 pulls out the ␣ chain from rafts to bind the ␤ and ␥ chain of the IL-2 receptor complex in soluble fractions (50). Hence, interleukins are involved in the rules governing the inclusion and exclusion of proteins into rafts.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, the localization of IL-2R␣, but not IL-2R␤ and ␥ to membrane rafts has been reported (37), but in another report all three subunits were localized to lipid rafts (38). In addition, one report showed that Abs to GM1, which is localized to lipid rafts, inhibited IL-2-mediated proliferation (37). Based on our study, we predict that IL-2R clustering will lead to recruitment of the ␤ and ␥ subunits into lipid raft domains, because CEACAM1 appears to reside within these microdomains, and the GM1 inhibition data are consistent with this conclusion.…”
Section: Colocalization Of Ceacam1-4l With Il-2r␤ and Il-2r␥mentioning
confidence: 98%
“…Integrity of lipid rafts is also essential for IL-2-mediated signaling (12,13). Lipid rafts may promote the formation and cytokine-specific modulation of IL-2R͞IL-15R complexes and ␤-and ␥ c -subunit ''switching'' between IL-2 and IL-15 receptors.…”
mentioning
confidence: 99%